IMPLEMENTATION OF KNOWLEDGE MANAGEMENT TO INCREASE COMPETITIVE ADVANTAGE TOWARDS EXPORTS (STUDY VISIT AT AIDA FURNITURE, PASURUAN) - Sudirman; Sudarmiatin Sudarmiatin; Imam Mukhlis (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
This study aims to find out how to implement knowledge management as an effort to increase competitive advantage towards exports. This research was conducted at Aida Furniture, Pasuruan, East Java, Indonesia. The research method was carried out using descriptive and qualitative analysis, by conducting direct interviews with company owners and direct observation of the company. This study obtained results indicating that the successful implementation of knowledge management in the Aida Furniture company was determined by leadership and management support, organizational culture, information technology innovation, training and education. This understanding will help companies to identify important issues that must be faced when designing and implementing knowledge management. This lack of understanding causes companies to be slow to compete with others making it difficult to export due to low internationalization performance.